THE ACTIVITY INFLUENCE USING GEOGEBRA PROGRAM ON CIRCLE SUBJECT OF STUDENT ACHIEVEMENT - Mohammad Syaiful Pradana (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2015)
Nowdays, education has support by modern facilities like a computer. So, this facilities should be utilized maximally, especially in mathematics. One of the computer program for learning mathematics is Geogebra. This program provides a geometric visualization to clarify certain concepts to students. The purpose of this research is determine the activity of learners using Geogebra program and its effect for students achievement. The research type is not purely experimental studies with one shot case studymodels. This is an experiment models conducted without comparison group and also preview test. The research population is students at XI MIA-1 until XI MIA-7 Senior High School 1 Manyar Gresik academic years 2014-2015. While the sample is XI MIA-2 randomly selected after homogenity test. The research instrument using observation sheet and test. From the data collected and analyzed using normality test, liniearity test, linear regression test, F test, t test and determination coefficient results regression equation